Q: How do you simplify 3b plus b plus 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

The equation (b2 - 2b) + (3b - 6) = b2 + b - 6

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1

if you meant to write the problem as "3b + 5 = 29", then this is how to solve: 3b + 5 = 29 - 5 - 5 subtract 5 from each side 3b = 24 simplify b = 8 divide each side by 3 to get b by itself

The answer to 4a times 3b equals 1.3. You have to find the value of A and B.

To simplify the expression 3b^2 - 3b, we first factor out the common factor of 3b. This gives us 3b(b - 1), where b - 1 is the simplified form of the expression. This expression represents the difference between 3 times the square of a variable b and 3 times the variable b.

Related questions

It is: b+4 when simplified

If a + b = 6, what is the value of 3a + 3b?

b times b times b = b3 b plus b plus b = 3b

3b + 6 = 12 3b = 6 b = 2

6

3b -1

The equation (b2 - 2b) + (3b - 6) = b2 + b - 6

b = -6

b = -8

20+3b = 20 + 3(-6) = 20-18 = 2

(a+b)(3b+1)

12a + 6b + 6c = 6(2a + b + c)